Stochastic analysis of the technical and financial impacts and economic feasibility of the integration of Distributed Solar Energy Systems with storage in real feeder - Togo, Henrique Augusto Gomes (2025)
Dissertação (mestrado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, Programa de Pós-Graduação em Engenharia Elétrica, 2025.